Oak masting breaks down in a highly fragmented, pollen-limited landscape - Ian S. Pearse; Jill H. Baty; Mario B. Pesendorfer; Robert Olson; Walter D. Koenig (Proceedings of the National Academy of Sciences, 2026)
Masting, the production of variable and synchronous seed crops, is common among wind pollinated trees, and periodic pollen limitation is thought to be an important component of the process of masting. However, little is known either about the dynamics of mast seed production or pollen limitation in isolated trees. We tracked seed production of valley oak ( Quercus lobata ) over 11 years in a highly fragmented landscape in California’s Central Valley in which many trees lacked conspecific neighbors within 500 m. We found that oaks with closer neighbors produced more acorns on average than oaks with fewer neighbors. Consistent with theories linking mast seeding and pollination, the isolation effect was most apparent in the highest seed production years. While individual trees showed substantial interannual variation in seed production, we observed little synchrony in seed production among individuals compared to intact oak populations throughout California. Our results indicate that highly fragmented populations suffer signs of pollen limitation and do not produce synchronous seed crops. Fragmentation, alongside climate change, is a dimension of global change that interrupts the typical seed production dynamics of trees.